Quasi-monopoly: A theoretical model to understand the state-private sector relationship in educational systems - Narodowski, Mariano; Morgan, Juan Carlos (Education Policy Analysis Archives, 2020)
The aim of this article is to present a detailed exposition of the theoretical model of the quasi-monopoly of educational systems. Rather than simply understanding private education in opposition to public education, the gathered evidence allows for the design of an equilibrium model that tends to a) maximize private spending as a way to raise the schooling rate, b) generate a private “exit” sector that presents a trade off with the traditional state sector in regards to decision making about the organization of the institutions, the use of resources, the curriculum, etc. and c) reproduce the stock as well as the flow of state resources to the traditional state sector, regardless of their needs, problems of inequality and cases of ineffective resource allocation. The paper presents the key concepts for the analysis and provides examples with data collected from previous investigations. Furthermore, a mathematical model is proposed to axiomatize the components of a quasi-monopoly in an educational system. Finally, the article offers different perspectives of analysis to use the theoretical model of the quasi-monopoly in an educational system for different national and sub-national cases.